Occurrence and Characterization of mcr-1-Positive Escherichia coli Isolated From Food-Producing Animals in Poland, 2011–2016 - Zając, Magdalena; Sztromwasser, Paweł; Bortolaia, Valeria; Leekitcharoenphon, Pimlapas; Cavaco, Lina M.; Ziȩtek-Barszcz, Anna; Hendriksen, Rene S.; Wasyl, Dariusz (Frontiers in Microbiology, 2019)
The emergence of plasmid-mediated colistin resistance (mcr genes) threatens the effectiveness of polymyxins, which are last-resort drugs to treat infections by multidrug- and carbapenem-resistant Gram-negative bacteria. Based on the occurrence of colistin resistance the aims of the study were to determine possible resistance mechanisms and then characterize the mcr-positive Escherichia coli. The research used material from the Polish national and EU harmonized antimicrobial resistance (AMR) monitoring programs. A total of 5,878 commensal E. coli from fecal samples of turkeys, chickens, pigs, and cattle collected in 2011–2016 were screened by minimum inhibitory concentration (MIC) determination for the presence of resistance to colistin (R) defined as R > 2 mg/L. Strains with MIC = 2 mg/L isolated in 2014–2016 were also included. A total of 128 isolates were obtained, and most (66.3%) had colistin MIC of 2 mg/L. PCR revealed mcr-1 in 80 (62.5%) isolates recovered from 61 turkeys, 11 broilers, 2 laying hens, 1 pig, and 1 bovine. No other mcr-type genes (including mcr-2 to -5) were detected. Whole-genome sequencing (WGS) of the mcr-1–positive isolates showed high diversity in the multi-locus sequence types (MLST) of E. coli, plasmid replicons, and AMR and virulence genes. Generally mcr-1.1 was detected on the same contig as the IncX4 (76.3%) and IncHI2 (6.3%) replicons. One isolate harbored mcr-1.1 on the chromosome. Various extended-spectrum beta-lactamase (blaSHV–12, blaCTX–M–1, blaCTX–M–15, blaTEM–30, blaTEM–52, and blaTEM–135) and quinolone resistance genes (qnrS1, qnrB19, and chromosomal gyrA, parC, and parE mutations) were present in the mcr-1.1–positive E. coli. A total of 49 sequence types (ST) were identified, ST354, ST359, ST48, and ST617 predominating. One isolate, identified as ST189, belonged to atypical enteropathogenic E. coli. Our findings show that mcr-1.1 has spread widely among production animals in Poland, particularly in turkeys and appears to be transferable mainly by IncX4 and IncHI2 plasmids spread across diverse E. coli lineages. Interestingly, most of these mcr-1–positive E. coli would remain undetected using phenotypic methods with the current epidemiological cut-off value (ECOFF). The appearance and spread of mcr-1 among various animals, but notably in turkeys, might be considered a food chain, and public health hazard.